Determination to Improve of Auditor Performance at the Financial Audit Agency Representing the Province of South Sumatra - Putra, Muhammad Dwi; Dewata, Evada; Saputri, Ulfah Tika (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
The performance of auditors is a very important element in an organization which assesses certain measures such as the quality of work, the amount of work completed and the timeliness planned, therefore individual performance can affect the work productivity of an organization. Auditor performance can also be influenced by internal and external factors which will affect how an auditor acts in making decisions, creating a reasonable opinion in accordance with the financial statements that occur. This study aims to analyze the role of emotional intelligence, time budget pressure and work-life balance on Auditor performance. This type of research uses primary data obtained from respondents' answers submitted to the Supreme Audit Agency of South Sumatra Province Representative. This research uses PLS-SEM software version 4.0. The results showed that Emotional Intelligence had no significant effect on auditor performance, while time budget pressure and work-life balance had a positive effect on auditor performance.